Students’ Responses Regarding the Use of Films in Learning Media during Online Classes in The Pandemic Era - Lidiya Rachmawati; Pratiwi Retnaningdyah; Ali Mustofa (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
The use of digital media in online learning requires teachers to be more innovative in attracting students' interest. However, the limited interaction and communication causes problems in students' understanding. This will result in passive student responses in online classes if online learning activities are not accompanied by innovative learning motivation. This study aims to help teachers apply a more innovative approach through audiovisual media in films to help students understand issues and create critical thinking expressed through written works. The student response approach to audiovisual learning has achieved surprising findings. Experiential approach Student response combined with the cognitive theory of multimedia learning brings students into a critical understanding of the experiences of fictional characters that are even different from their lives. The findings indicate that students are more interactive and critical in responding to the issues in the film. The use of audiovisual media as digital literature through films is considered effective in developing knowledge, emotional experiences, and increasing students' social awareness. Although some compassionate students have difficulty expressing their emotions, most of them give a positive response in this method. The teacher stated that it took more time to prepare the material. In the interview, the teacher realized the changes in students' attitudes and communication, both verbally and in writing developed